Analisis NPF dan efisiensi operasional sebagai penentu kinerja keuangan Bank Muamalat 2020-2024 - syahlatunnisa, syifa; AISYAH, ESY NUR (Maliki Interdisciplinary Journal, 2026)
this study investigates changes in Bank Muamalat Indonesia’s Non-Performing Loan (NPF) during the 2020-2024 period, which serves as an indicator of the health of Islamic banking. The NPF decreased to 0.67% (2021) as a result of post-pandemic restructuring, then increased again to 2.78% (2022), 2.06%(2023), and reached 3.35% (2024). The main results indicate a significant negative relationship betwrrn NPF and profitability (ROA), where increasing non-performing financing negatively impacts profitability. Although NPF has shown improvement, ROA remains low (0.02-0.22%) due high BOPO (96%-99%), which reflects poor operational efficiency. Elements influencing NPF include internal factors (cost rfficiency, financing management quality, capital structure) and external factors (the COVID-19 pandemic and the macroeconomic situation). This study concludes that a decrease in NPF alone is not sufficient to improve bank performance without a sustained increase in efficiency and profitability.